Multiplicative calculus and its applications - Bashirov, Agamirza E.; Kurpinar, Emine Misirli; Ozyapici, Ali (Academic Press Inc Elsevier Science, 2008)
Two operations, differentiation and integration, are basic in calculus and analysis. In fact, they are the infinitesimal versions of the subtraction and addition operations on numbers, respectively. In the period from 1967 till 1970 Michael Grossman and Robert Katz gave definitions of a new kind of derivative and integral, moving the roles of subtraction and addition to division and multiplication, and thus established a new calculus, called multiplicative calculus. In the present paper our aim is to bring up this calculus to the attention of researchers and demonstrate its usefulness. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: calculus; derivative; integral; limit; semigroup; differential equation; calculus of variations